PEMBANGUNAN INDUSTRI PENAMBANGAN DAN PENGOLAHAN PASIR BESI SERTA IMPLIKASINYA TERHADAP KETAHANAN EKONOMI WILAYAH (Studi Di Kabupaten Kulon Progo Daerah Istimewa Yogyakarta) - Ndaru Sukmono Aji (Universitas Gadjah Mada, 2014)
Mining industry and iron-bearing sand in Kulonprogo Regency area was a mining project with large budget investment, namely Rp. 5.4 – 6 trillions, Working Contract area 2,987.79 hectares, and 2,100 people workers. The purpose of this research was to found out the iron-bearing and industry development in Kulonprogo Regency and its implication on economic resilience of region development at Kulonprogo DIY. The research was conducted with qualitative descriptive method and the collected data of the field observation and questionnaire for the respondents based on the purposive sampling method. Mining industry and iron-bearing sand processing implication on economic resilience at Kulonprogo Regency area was conducted by recruiting workers, entrepreneur’s chance, and land compensation payment, agricultural production harvest and its infrastructure. Local government gained profit from tax, retribution, royalties, regional development budget, community developing budget therefore the regional revenue increasing.Keywords: Development, Maining and Iron-Bearing Sand Processing, Economic Resilience of Region.